2006
DOI: 10.1080/15572536.2006.11832643
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships of Japanese species ofHeterobasidion—H. annosum sensu latoand an undeterminedHeterobasidionsp.

Abstract: The phylogenetic relationships of two Japanese Heterobasidion species, H. annosum sensu lato and an undetermined species, were revealed based on three gene loci, glyceraldehyde 3-phosphate dehydrogenase (gpd), heat shock protein (hsp) and elongation factor 1-alpha (ef). The tree, based on combined data of gpd, hsp and ef, showed that Japanese H. annosum s.l. was close to the European S-group, forming a subclade. The results of this study also provided strong support for the recognition of the undetermined Hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Phylogenetic studies based on three gene loci revealed that Japanese H. annosum s. lat. is also closely related to European and Chinese populations of H. parviporum (Ota et al 2006).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Phylogenetic studies based on three gene loci revealed that Japanese H. annosum s. lat. is also closely related to European and Chinese populations of H. parviporum (Ota et al 2006).…”
Section: Introductionmentioning
confidence: 91%
“…The phylogenetic relationships of this fungus in the genus of Heterobasidion were revealed by Ota et al (2006) as "H. insulare". Heterobasidion orientale is characterized by annual and sessile to effused-refl exed basidiocarps, semicircular to fl abelliform and applanate pilei, reddish brown and glabrous pileus surface with white margin, thin crust on the pileus surface, and angular to round or labyrinthiform pores.…”
Section: Heterobasidion Orientalementioning
confidence: 98%
See 1 more Smart Citation
“…parviporum Niemelä & Korhonen (= European S intersterility group) characteristically causes butt and heart decay in Norway spruce, but also attacks other conifers, and is highly infectous to Abies sibirica in Eastern Europe (Korhonen 1978a, Korhonen and Dai 2005, Dai et al 2006. The H. parviporum taxonomical cluster (see Study I, Dai et al 2006) appears to have a continuous distribution range from Europe through southern Siberia to northern China, and related isolates have recently been found also in Japan (Ota et al 2006). In turn, H. abietinum Niemelä & Korhonen (= European F intersterility group) has a relatively restricted distribution ranging from southern and central Europe to western Turkey and Russian Caucasus, and mainly occurs on Abies spp.…”
Section: Heterobasidion Annosum Species Complexmentioning
confidence: 99%
“…It is also likely that even more species of Heterobasidion occur in South-Eastern Asia (particularly China or India). In Japan, a new species of Heterobasidion has been recently discovered (Ota et al 2006). …”
Section: Heterobasidion Annosum Sl (I)mentioning
confidence: 99%